surrounded by psychopaths Or, How to Stop Being Exploited by Others - Erikson, Thomas (Vermilion, an imprint of Ebury Publishing, 2020)
Some people are exceptionally manipulative. They can convince anyone about anything and lure them with their charm. They enjoy controlling others and will do anything to get what they want. Sound familiar? The bad news is that you can't really escape them. But here comes the good news: you can beat them at their own game. After going through the highs and lows of different personality types (Red, Blue, Green and Yellow) in his international bestseller Surrounded by Idiots, Swedish behavioural expert Thomas Erikson will now show you how your weaknesses and personality traits can be exploited by other people and how you can stop them in their tracks. By learning more about your personality type and how you work, you'll be able to see through any psychopath's manipulative behaviours and fend off their attempts to wreak havoc into your life. Witty, engaging and informative, this book will give you everything you need to handle life's most skilled manipulators and identify the psychopaths in your life... before it's too late!